"You Shouldn t Have Done That": "Ben Drowned" and the Uncanny Horror of the Haunted Cartridge - Sanders, John (Gamevironments, 2018)
Written on 4Chan message boards by a user named Jadusable (Alex Hall) in 2010 and later archived by creepypasta enthusiasts, Ben Drowned relates the saga of a college sophomore s encounter with a bootleg copy of The Legend of Zelda: Majora s Mask (2000) supposedly possessed by the spirit of its former owner. Over the course of two weeks, Jadusable records his experiences in writing and short videos as the entity within the cartridge torments him, eventually taking control of his technology and escaping into the Internet. After a brief overview of theories of the uncanny and haunted media, this paper will conduct a narratological analysis of the Ben Drowned saga in order to explore the aesthetic and social potential of haunted cartridge narratives, especially how they can reveal the inherent uncanniness of games as a medium. Haunted cartridge narratives like Ben Drowned help to elucidate unsettling ambiguities between data and spirit, save files and human identity. Through stories like these, the information-carrying cartridge is revealed to mirror the body/soul duality so familiar to humanity, housing data, which may be possessed, altered, and corrupted by entities unknown. The errors and glitches commonplace in contemporary gaming technologies are recast within the work as being of uncertain and perhaps malicious origins, distorting once familiar digital spaces with the disquieting efficiency of an unseen hand. As such, this under-analyzed piece of digital fiction resonates with cultural fears regarding the primacy of incorporeal information within contemporary network society and casts the medium of the video game as a space ripe for encounters with uncanny entities.